ANALISIS ETOS KERJA PETANI DALAM TRADISI "BELALLE"™" DIDESA GAPURA, KECAMATAN SAMBAS, KABUPATEN SAMBAS - ANSARI, SISKA; Mashudi, Mashudi; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The objective of this study is to ascertain : (1) The work ethic of farmers in Gapura Village, Sambas District, Sambas Regency in the Belalle' tradition (2) the economic values of the Belalle' tradition in Gapura Village (3) Factors influencing the work ethic of farmers in the village Gate. This research employs a qualitative methodology with a descriptive approach. The data collection process comprises observation, interviews, and documentation. The tools used to collect information include observation guides, interview guides, and documentation tools. The data analysis was conducted by adhering to the stages of data reduction, data presentation, and drawing conclusions. To ensure data validity, extended observations and triangulation of information sources were conducted. Based on the results of this research, it can be concluded that.: (1) The work ethic of farmers in Gapura Village, Sambas District, Sambas Regency is high. This is evidenced by farmers with signs indicating someone with a high work ethic. (2) The economic values contained in the work ethic of farmers in Gapura Village, Sambas District, Sambas Regency reduce production costs, facilitate the production process, increase profits, save production costs, do not need to pay labor wages, and do not buy consumption. (3) The factors influencing the work ethic of farmers can be categorized into two groups, namely supporting factors including high tolerance, social interaction, mutual assistance, mutual cooperation and Enhancing the economy serves as a facilitating factor, while inhibiting factors include the rise of individualism and differing attitudes among individuals.